2023
DOI: 10.1021/acs.jpclett.2c03294
|View full text |Cite
|
Sign up to set email alerts
|

One Ca2+ Site in CaNaY Zeolite Can Attach Three CO2 Molecules

Abstract: To design efficient CO2 capture materials, it is necessary to ensure a high adsorption capacity. We recently reported that one Na+ site in NaY zeolite can attach two CO2 molecules. However, the process is not suitable for practical use because it proceeds at a low temperature. Here, we present results on CO2 adsorption on CaNaY zeolites, demonstrating that one Ca2+ site can attach three CO2 molecules. The ν3(13CO2) mode arising from the natural 13C abundance allows for easy infrared monitoring of the processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…In the pilot communication to this study [ 23 ], we reported that indeed three CO 2 molecules can be attached to one Ca 2+ site in CaNaY. The one-ligand Ca 2+ –OCO species are produced at very low equilibrium pressure.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…In the pilot communication to this study [ 23 ], we reported that indeed three CO 2 molecules can be attached to one Ca 2+ site in CaNaY. The one-ligand Ca 2+ –OCO species are produced at very low equilibrium pressure.…”
Section: Introductionmentioning
confidence: 75%
“…The ν 3 ( 13 CO 2 ) satellite band is observed at 2298 cm −1 [ 37 ] and is shifted to 2293.5 cm −1 with coverage increase. In addition, we detected the (ν 1 + ν 3 )( 12 CO 2 ) and (2ν 2 + ν 3 )( 12 CO 2 ) combination modes [ 14 , 23 , 37 ], which at high coverage appeared at 3715 and 3604 cm −1 , respectively (see the upper inset in Figure 3 ). Two more bands were recorded at lower frequencies, at 1379 and 1270 cm −1 (see the lower inset in Figure 3 ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations